Cetuximab plus irinotecan versus panitumumab in patients with refractory metastatic colorectal cancer in Ontario, Canada. Issue 9 (1st May 2017) - Jerzak, Katarzyna J.; Berry, Scott; Ko, Yoo‐Joung; Earle, Craig; Chan, Kelvin K. W.
Abstract : The addition of irinotecan to an epidermal growth factor receptor (EGFR) antibody has previously been shown to improve tumor response rate and time to progression but not overall survival (OS) for refractory metastatic colorectal cancer (mCRC). We assessed the "real‐world" effectiveness and toxicity of the combination versus monotherapy. In Ontario, Canada, universal public funding is available for either cetuximab plus irinotecan (Cmab + I) combination therapy or panitumumab (Pmab) monotherapy, only in patients with refractory nonmutated RAS mCRC. All patients diagnosed before December 2012 and treated with an EGFR antibody for mCRC were identified from the Ontario drug database and linked to the Ontario Cancer Registry and other administrative databases to ascertain baseline characteristics, health services utilization, and outcomes. Multivariable Cox and logistic models were constructed to compare the time to treatment discontinuation (TTD), OS, emergency department (ED) or hospital visits between Cmab + I and Pmab. Observable confounders were adjusted for using propensity score methods. One thousand and eighty‐one patients were identified (Cmab + I: 278, Pmab: 803). Patients receiving Cmab + I were younger (mean age 61 vs 64 years) and had a longer duration of prior irinotecan treatment. The use of Cmab + I as compared to Pmab alone was associated with a prolonged TTD [median: 3.8 months vs 2.8 months] and an improved OS [median: 8.8 months vs. 5.9 months] with an adjusted HR of 0.62 [95% CI 0.53–0.73, p < 0.001]. Both treatment regimens afforded similar 14‐day mortality and incidence of ED or hospital visits. The findings for patients over and below the age of 65 were similar. Abstract : What's new? Drugs targeting the epidermal growth factor receptor (EGFR) serve a critical role in the treatment of metastatic colorectal cancer (mCRC). Their effectiveness, however, is undermined by mutations in the KRAS oncogene. This study compared the effectiveness and toxicity of the EGFR‐directed antibodies panitumumab, used alone, versus cetuximab, used in combination with irinotecan, in patients with refractory, nonmutated KRAS mCRC. Combination therapy yielded superior improvements in overall survival, warranting its consideration for use in irinotecan‐tolerant mCRC patients. Measures of toxicity, including 14‐day mortality and 30‐day incidence of hospitalization, were similar in both groups, irrespective of age.